From RTBF to Devoir de Mémoire: The Imperative of Amanah and Adālah in Regulating Former Corruption Offenders' Candidacy - Santono, Agung Nugroho Reformis; Abrori, Muhammad Burhan; Azizi, Muhamad Lutfi; Ramadhani, Moch. Rafly Try (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2025)
The Indonesian regulation permitting ex-corruption convicts to run for public office after a five-year waiting period creates a critical normative dilemma, particularly when intersecting with the EU-centric' Right to Be Forgotten' (RTBF). This article explicitly aims to analyze and challenge the applicability of the RTBF framework to the candidacy of former corruption offenders by re-examining it through the lens of Islamic leadership ethics, specifically the principles of amanah, adālah, and fiqh siyasah. Using a normative-juridical approach, this study analyzes Indonesian electoral regulations and the RTBF doctrine, synthesized with classical and contemporary Islamic jurisprudence, with particular emphasis on Maqāshid al-Sharīʿah and the doctrine of sadd al-dharāʿīʿ. The findings reveal two key points: First, the five-year waiting period fundamentally misapplies RTBF by equating public records of corruption with private data; this article proposes its antithesis, devoir de mémoire (the duty to remember), as the required public policy framework. Second, Islamic jurisprudence establishes adālah (moral integrity) as a binding legal qualification (sharṭ) for public office, and corruption legally and perpetually nullifies this qualification. The study concludes that spiritual taubah (repentance) is distinct from public-legal qualification (ḥaqq al-ummah) and does not automatically restore eligibility. Therefore, disqualifying former corrupt officials does not violate rights but represents a necessary implementation of sadd al-dharā’iʿ to safeguard public amanah and protect the public interest.